Analysis of processes of friction at high-rate of sliding. - Писаренко, В.Г.; Медведчук, Н.К. (Problems of Tribology, 2015)
On the basis of the conducted analysis of criteria of high-speed friction the offered method of estimation of effi-ciency of technologies of increase of wearproofness is on the basis of analysis of functional dependences the coefficient of friction from speed of sliding. The examples of experimental realization offered approach are resulted for the different meth-ods of strengthening of surfaces of steel standards